The Chicken or the Egg? : Endogeneity in Labour Market Participation of Informal Carers in England - Axel Heitmüller (Institute for the Study of Labor (IZA), 2004)
Informal care is a vital pillar of the British welfare state. A well-known fact in the small economic literature on informal care is the apparent negative relation between care responsibilities and labour market participation. Yet, caring and labour market participation may be endogenous. Using an instrumental variable approach and data from the British Household Panel Study for 2002 this paper shows that not accommodating for endogeneity in the labour market participation equation may significantly underestimate the impact care exhibits on the employment decision of informal carers. This is the more the case the smaller the choice of becoming a carer. Policy implications are derived.
Keywords: C10; J22; I11; 330; instrumental variable approach; informal care; endogeneity; labour market participation; Pflegedienst; Informeller Sektor; Arbeitsangebot; Grossbritannien